2020
DOI: 10.2967/jnumed.120.242248
|View full text |Cite
|
Sign up to set email alerts
|

Data-Driven Respiratory Gating Outperforms Device-Based Gating for Clinical 18F-FDG PET/CT

Abstract: Methods 144 whole-body 18 F-FDG PET/CT examinations were acquired using a Discovery D690 or D710 PET/CT scanner (GE Healthcare), with a respiratory gating waveform recorded by an external, device-based respiratory gating system. In each examination, two of the bed positions covering the liver and lung bases were acquired with duration of 6 minutes. Quiescent period gating retaining ~50% of coincidences was then able to produce images with an effective duration of 3 minutes for these two bed positions, matching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 26 publications
3
48
1
Order By: Relevance
“…4. This result is in contradiction with Walker et al (Walker et al 2020) who however only visually investigated the noise level in the liver and bone marrow in PET/CT data and found almost equivalent noise levels in images based on DDG, external hardware gating, and a static image from 50% of the coincidence data. In another study, evaluating respiratory gating based on signals extracted from PET raw data using PCA, the results showed significantly lower noise levels in images based on respiratory gating signals extracted from PET raw data using PCA compared with gated images based on respiratory gating signals extracted from external bellow device (Fürst et al 2015).…”
Section: Discussioncontrasting
confidence: 96%
“…4. This result is in contradiction with Walker et al (Walker et al 2020) who however only visually investigated the noise level in the liver and bone marrow in PET/CT data and found almost equivalent noise levels in images based on DDG, external hardware gating, and a static image from 50% of the coincidence data. In another study, evaluating respiratory gating based on signals extracted from PET raw data using PCA, the results showed significantly lower noise levels in images based on respiratory gating signals extracted from PET raw data using PCA compared with gated images based on respiratory gating signals extracted from external bellow device (Fürst et al 2015).…”
Section: Discussioncontrasting
confidence: 96%
“…Limitations of this study includes that no comparison of DDG versus device-based gating was performed. This has, however, been published previously on retrospective [ 18 F]FDG data, in terms of evaluating the respiratory signal, quantitative measurements and image quality, and where the performance of DDG was found superior [15]. Further, the PET/CT findings were not validated by comparison with a standard of reference.…”
Section: Discussionmentioning
confidence: 77%
“…The respiratory signal generated with PCA-based DDG has been found to correlate well with that from devices, and showed better performance in terms of robustness, image quality, and higher standardized uptake values (SUV). Introduction of DDG into PET clinics might allow for replacement of device-based gating and make routine use of respiratory gating clinically feasible [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Existing researches suggested that respiratory movement leads to overestimations of radiotracer-avid target volume and reduction in the SUV due to the recorded number of coincidence events tending to distribute in a larger volume 28 . A data-driven respiratory gating function is now available on the GE system, which has shown out-performance than the device-based gating 29 . The respiratory gating system can be employed in a future study to facilitate the improvement of spatial resolution and quantification accuracy, especially when radiotherapy treatment planning is desired 30 32 .…”
Section: Discussionmentioning
confidence: 99%